The partially folded conformation of the Cys-30 Cys-51 intermediate in the disulfide folding pathway of bovine pancreatic trypsin inhibitor. - van Mierlo, C P (1992)
The best-characterized protein folding pathway is that of bovine pancreatic trypsin inhibitor, which folds from the reduced form through a series of disulfide bond intermediates. The crucial one-disulfide intermediate of bovine pancreatic trypsin inhibitor with the disulfide bond between Cys-30 and Cys-51 is shown here to have a partially folded conformation in which the major elements of secondary structure interact via a core of apolar side chains, which resembles part of the native conformation. The stability of this structure can account for the predominance of this one-disulfide intermediate during folding. Much of the remaining one-third of the polypeptide chain, in particular the N-terminal 14 residues, is largely disordered; this accounts for the ability of this intermediate to form readily any of the three possible second disulfide bonds involving Cys-5, -14, and -38. The partially folded conformation of this intermediate provides direct evidence for the importance of native-like interactions between elements of secondary structure in directing protein folding, which is assumed in many studies.